Potentiometric evaluation of calix[4]arene anion receptors in membrane electrodes: Phosphate detection - Kivlehan, F.; Mace, W.; Moynihan, H.; Arrigan, Damien (Elsevier BV, 2007)
Ion-selective electrodes (ISEs) allowthe potentiometric sensing of the activity of specific ions in the presence of other ions. They belong to the oldest established group of chemical sensors and their behaviour is generally well understood, founded on basic thermodynamic and kinetic processes [1–5]. ISEs containing polymeric membranes, such as poly(vinyl chloride) (PVC), which are assumed to behave as organic liquids of high viscosity, are by far the most versatile and widely studied class of ISEs. In order to obtain highly selective ISEs on the basis of PVC membranes, suitable ionophores must be doped into these membranes